In vivo antidiabetic activity of nimesulide due to inhibition of amino acid transport. Issue 1 (25th October 2021) - Joharapurkar, Amit; Kshirsagar, Samadhan; Patel, Vishal; Patel, Maulik; Savsani, Hardikkumar; Jain, Mukul
Abstract: Inhibiting the intestinal and renal neutral amino acid transporter B0AT1 by genetic means has improved insulin sensitivity in mice, but there are no antagonists available for preclinical or clinical use. Since the anti‐inflammatory agent nimesulide selectively inhibited B0AT1 in vitro, we hypothesized that nimesulide exhibits in vivo potential to restrict neutral amino acid absorption and, therefore, may improve insulin sensitivity. The dose‐related effect of nimesulide (10 to 100 mg/kg, PO) on intestinal absorption of neutral amino acids was estimated in C57 mice. The effect of nimesulide (50 mg/kg, PO) on renal resorption of amino acids was also assessed. The effect of chronic nimesulide (50 mg/kg, PO, BID for 14 days) was assessed in high protein diet‐fed C57 mice, diet‐induced obese mice and obese and diabetic db/db mice. Acute and chronic nimesulide treatment decreased absorption of neutral amino acids and increased their urinary excretion. Nimesulide treatment improved insulin sensitivity and glycemic control, increased GLP‐1, decreased liver lipids and improved FGF‐21 in serum. Nimesulide improved insulin sensitivity and glucose tolerance by inhibiting neutral amino acid transport in the intestine and kidneys. Thus, it can serve as a tool compound for in vivo B0AT1 inhibition.